Electrophysiological evidence for the characteristics of implicit self-schema and other-schema in patients with major depressive disorder: An event-related potential study - Yao, Jia-yu; Zheng, Zi-wei; Zhang, Yi; Su, Shan-shan; Wang, Yuan; Tao, Jing; Peng, Yi-hua; Wu, Yan-ru; Jiang, Wen-hui; Qiu, Jian-yin (Frontiers in Psychiatry, 2023)
Background: The significance of implicit self-schema and other-schema in major depressive disorder (MDD) is highlighted by both cognitive theory and attachment theory. The purpose of the current study was to investigate the behavioral and event-related potential (ERP) characteristics of implicit schemas in MDD patients. Methods: The current study recruited 40 patients with MDD and 33 healthy controls (HCs). The participants were screened for mental disorders using the Mini-International Neuropsychiatric Interview. Hamilton Depression Rating Scale-17 and Hamilton Anxiety Rating Scale-14 were employed to assess the clinical symptoms. Extrinsic Affective Simon Task (EAST) was conducted to measure the characteristics of implicit schemas. Meanwhile, reaction time and electroencephalogram data were recorded. Results: Behavioral indexes showed that HCs responded faster to positive self and positive others than negative self (t=-3.304, p=0.002, Cohen’s d=0.575) and negative others (t=-3.155, p=0.003, Cohen’s d=0.549), respectively. However, MDD did not show this pattern (p>0.05). The difference in other-EAST effect between HCs and MDD was significant (t=2.937, p=0.004, Cohen’s d=0.691). The ERP indicators of self-schema showed that under the condition of positive self, the mean amplitude of LPP in MDD was significantly smaller than that in HCs (t=-2.180, p=0.034, Cohen’s d=0.902). The ERP indexes of other-schema showed that HCs had a larger absolute value of N200 peak amplitude for negative others (t=2.950, p=0.005, Cohen’s d=0.584) and a larger P300 peak amplitude for positive others (t=2.185, p=0.033, Cohen’s d=0.433). The above patterns were not shown in MDD (p>0.05). The comparison between groups found that under the condition of negative others, the absolute value of N200 peak amplitude in HCs was larger than that in MDD (t=2.833, p=0.006, Cohen’s d=1.404); under the condition of positive others, the P300 peak amplitude (t=-2.906, p=0.005, Cohen’s d=1.602) and LPP amplitude (t=-2.367, p=0.022, Cohen’s d=1.100) in MDD were smaller than that in HCs. Conclusions: Patients with MDD lack positive self-schema and positive other-schema. Implicit other-schema might be related to abnormalities in both the early automatic processing stage and the late elaborate processing stage, while the implicit self-schema might be related only to the abnormality in the late elaborate processing stage.